Predictors of Online Learning Satisfaction Among Filipino Pre-service Teachers: A Stepwise Multiple Regression Analysis - Adamos, Joel (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study investigated the predictors of online learning satisfaction among Filipino pre-service teachers in a comprehensive Philippine university, focusing on online authentic learning self-efficacy, social interaction, social presence, and collaborative learning. Anchored in the Community of Inquiry Framework and the Self-determination Theory, this research employed a descriptive-correlational design, using multivariate correlations and multiple regression analysis to assess the relationships among key variables. Quantitative data were collected from 302 pre-service teachers, revealing that social interaction, collaborative learning, and online authentic learning self-efficacy significantly contribute to online learning satisfaction, with age also playing a considerable role. The dimension of self-efficacy related to keeping up with technological advancements had the highest mean rating, while the dimension concerning the relation with real-life environments and online interaction had the lowest mean. Social presence and collaborative learning had moderate mean scores, whereas social interaction was rated lower. Nonetheless, social interaction and collaborative learning emerged as the strongest predictors of satisfaction, with social presence showing no significant impact. The results highlight the need to improve social interaction and collaborative elements in online learning settings to address the needs of Filipino pre-service teachers more effectively.